Family Sense of Coherence Scale: A Confirmatory Factor Analysis in a Portuguese Sample - Carneiro, Francis Anne T.; Salvador, Vanessa F.; Costa, Pedro A.; Leal, Isabel P. (Frontiers in Psychology, 2022)
Background: Family Sense of Coherence (FSOC) can be defined as a family’s cognitive map that enables the family to deal with stress during their lifetime. FSOC is the degree to which a family perceives family life as comprehensible, manageable and meaningful. To the best of our knowledge few studies have used this scale and very few have evaluated FSOC Scale psychometric properties. Objective: This study aimed to evaluate the psychometric properties of original FSOC Scale in a sample of Portuguese caregivers of children aged between 10 to 15 years. Method: A total of 329 caregivers completed a sociodemographic questionnaire and the FSOC Scale. Analyses were performed to evaluate the factor structure of the FSOC Scale with 26 items as well as composite reliability, internal consistency, convergent-related validity and discriminant-related validity of the scale scores. Results: The findings supported a three-factor solution for a 13-item version that maintains the original FSOC Scale structure proposed by Antonovsky and Sourani (1988). The three FSOC dimensions presented a good fit to the data. Cronbach’s alpha, composite reliability and convergent-related validity were considered very good for the FSOC Scale (α = .956; CR = .974; AVE = .689). No evidence of discriminant-related validity was found for FSOC’s dimensions. Conclusion: The findings support the use of the Portuguese FSOC Scale for research and clinical purposes with Portuguese caregivers. Future research is necessary to further develop a European Portuguese version of FSOC Scale. Implications: This study provides a psychometric evaluation of FSOC Scale characteristics in a Portuguese sample. The results are helpful for clinicians and family therapists who work with families since it could help them to assess families’ resources and ability to cope with adversity and enhance their strengths.